Galletas con base en concentraciones de harina de camote (Ipomoea batata l) y maíz (Zea mays) en el cantón Pichincha. - Gavilanez Saltos, Josselyn Stephania (2017)
Our country has a great variety of agricultural products including sweet potato that has great nutritional benefits. The sweet potato is a purple root, weighing between 500g; its flesh is soft, sugary and rich in starches. Currently the flour industry is conducting research to partially substitute wheat flour for non-traditional flours, with the aim of giving added value to other products, being here where the present research seeks to make known to the population a new alternative of free consumption Of gluten as are cookies of sweet potato flour and corn, since in addition to being a new product has vitamins and minerals that are beneficial to health. As regards the process of preparation of the cookies, the technical standards for the study were taken into account, which yielded good results, both in physical-chemical, microbiological and sensory analysis. The results of the physical-chemical analyzes of the cookies based on concentrations of sweet potato flour and maize flour were found according to the established standards, which give the safety of consumer safety, being these in the variable moisture, the optimum is T2 with (5.24%), which will have a longer shelf life; In dry matter T1 with (89.6%) shows the smallest amount and T2 with (94.74%) being the highest; The highest values of fiber and ash (2.382%), fat (17.294%), protein (6.412%), fiber (2.23%) and energy (441.34 kg) Protein are optimal; In the sensorial evaluation it was determined that the treatment of greater acceptability was the T1 standing out among the other treatments. For the accomplishment of the microbiological analyzes, the best treatment based on the sensorial evaluation was taken into consideration, which was the T1 determining that the analysis of mesophilic aerobes presented 977 cfu / g; In the analysis of total coliforms, present absence and in the analysis of molds and yeasts 65 cfu / g, all these data are within the norms NTE INEN 2085: 2005.